2002
DOI: 10.1182/blood.v99.3.822
|View full text |Cite
|
Sign up to set email alerts
|

Therapy-related myelodysplastic syndrome–acute myelogenous leukemia in patients treated for acute promyelocytic leukemia: an emerging problem

Abstract: The use of all-trans retinoic acid (ATRA) in combination with chemotherapy has markedly improved the prognosis for patients with acute promyelocytic leukemia (APL); the higher complete remission (CR) and survival rates now reported in this disease almost approach those obtained for other highly curable hematologic malignancies. Of 77 patients with APL who were consecutively treated at a single institution and who achieved CR after induction and consolidation therapy, 5 (6.5%) acquired therapy-related myelodysp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
79
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(83 citation statements)
references
References 24 publications
2
79
2
Order By: Relevance
“…Moreover, Nabhan and Radhakrishnan, [13] in their review article emphasized the fact that no published literature exists till date implicating 6-MP or methotrexate in causing severe AA even when these agents were employed for therapy of other disorders. Also Latagliata and co-authors in their report of five cases of t-MDS-AML following APL treatment in a cohort of 77 patients who achieved CR, suggested that APL treatment is not relevant in inducing the onset of secondary non-hematological malignancies [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Nabhan and Radhakrishnan, [13] in their review article emphasized the fact that no published literature exists till date implicating 6-MP or methotrexate in causing severe AA even when these agents were employed for therapy of other disorders. Also Latagliata and co-authors in their report of five cases of t-MDS-AML following APL treatment in a cohort of 77 patients who achieved CR, suggested that APL treatment is not relevant in inducing the onset of secondary non-hematological malignancies [14].…”
Section: Discussionmentioning
confidence: 99%
“…The evolution of other clonal disorders such as PNH, MDS and AML in AA patients treated with immunosuppressive therapy has since been well recognized [3,4,6]. Similarly secondary MDS or AML developing following treatment of APL is also documented in the literature [10,14]. A primary insult to the bone marrow could simultaneously lead to several abnormal hematopoietic cell clones, with one dominating and others present below the threshold of detection.…”
Section: Discussionmentioning
confidence: 99%
“…In APL patients, t-MDS and t-AML are sporadically reported [1,2], which were observed in about 6.5 % patients [3]. Patients usually developed t-MDS or t-AML with a latency ranging from 22 to 46 months after receiving chemotherapy [3].…”
Section: Discussionmentioning
confidence: 99%
“…Patients usually developed t-MDS or t-AML with a latency ranging from 22 to 46 months after receiving chemotherapy [3]. Cytogenetic abnormalities such as losses or deletions of chromosome 7 and/or 5 and recurrent balanced translocations involving 11q23 and 21q22 are frequently observed in t-AML and t-MDS, and are regarded as important hallmarks for the diagnosis of these two entities [4].…”
Section: Discussionmentioning
confidence: 99%
“…With increasingly successful treatment of malignancies, therapy-related leukemia (TRL) and myelodysplastic syndrome (MDS) are increasingly observed, especially in association with prior radiotherapy, use of alkylating agents or topoisomerase-II inhibitors [1,2]. They are characterized by lesions of chromosomes 5 and 7 and poor survival (median 7-10 months) [3,4].…”
Section: Dear Editormentioning
confidence: 99%